Soil enzymology - Shukla, Girish; Varma, Ajit (Springer Berlin Heidelberg Imprint: Springer, 2011)
Enzymes are one of the vital key mediators involved in nutrient recycling and the decomposition of organic matter and thereby in maintaining soil quality and fertility. This Soil Biology volume covers the various facets of soil enzymes, such as their functions, biochemical and microbiological properties and the factors affecting their activities. Enzymes in the rhizosphere, in forest soils, and in volcanic ash-derived soils are described. Soil enzymes covered include phosphohydrolases, lignocellulose-degrading enzymes, phenol oxidases, fungal oxidoreductases, keratinases, pectinases, xylanases, lipases and pectinases. Several chapters treat the soil enzymatic activities in the bioremediation of soils contaminated with pesticides and pollutants such as oil, chlorinated compounds, synthetic dyes and aromatic hydrocarbons. The role of soil enzymes as bioindicators is a further important topic addressed.